Ethanolic Extract of Papaya (Carica papaya) Leaves Improves Blood Cholesterol Profiles and Bone Density in Ovariectomized Rats - Sugiyanto, Raisatun Nisa; Khamsita, Rahmi; Susidarti, Ratna Asmah (Indonesian Journal of Cancer Chemoprevention, 2012)
Bone  loss  and  disturbance  in  the  blood  cholesterol  profiles  modulation  are  two effects  caused  by  menopauses  syndromes.  As  the  estrogen  concentration  in  the  body decreased  drastically,  menopause  women  need  the  replacement  of  estrogen  to  keep  the regulation  of  several  physiological  functions  in  the  body,  such  as  bone  generation  and cholesterol  regulation  in  a  good  condition.  Phytoestrogen  in  Carica  papaya  leaves,  such  as quercetin,  could  be  one  of  the  potential  agents  for  the  estrogenic  effect.  The  aim  of  this study  is  to  know  the  effects  of  papaya  leaf  extract  (PLE)  on  the  blood  cholesterol  profiles and bone density in ovariectomized rats. Thirty six female Sprague Dawley rats divided into six groups.  The groups were sham-treated ovx (S-OVX), ovariectomized rats (OVX), CMC-Na  control  (OVX+CMC-Na),  positive  control  (OVX+Estradiol),  and  the  PLE  treatment groups  dose  750  mg/kgBW  (OVX+750mg/kgBW)  and  dose  1000  mg/kgBW  (OVX+1000 mg/kgBW).  Administrations  of  PLE  were  done  in  three  weeks  orally  and  estradiol administrated  intraperitonially.  In  the  end  of  the  treatment,  the  blood  sample  of  tested animals was collected for the blood cholesterol  determination (LDL, HDL, triglyceride, and total  cholesterol)  and  the  femur  bones  were  examined  for  the  bone  density.  Based  on  the results, PLE  dose of 750 mg/kgBW a day in ovariectomized rats showed estrogenic effects in modulating  blood  cholesterol  profile  by  lowering  total  cholesterol  levels.  Meanwhile,  PLE dose  of  1000  mg/kgBW  significantly  increased  the  bone  density  (p<0.05).  Thus,  PLE  is potential  to  overcome  the  negative  effects  of  post-menstrual  women  especially  in  the cholesterol blood profiles and bone density.Keywords : Carica papaya, phytoestrogen, bone density, blood cholesterol, ovariectomized rats